Investigations of Viscous Dissipation in Stagnation Point Flow Past a Stretchable Riga Wall: Modern Analysis of Heat Transport. (April 2019) - Anjum, Aisha; Mir, N. A.; Farooq, M.; Javed, M.; Ahmad, S.
Abstract: This article scrutinizes the features of viscous dissipation in the stagnation point flow past through a linearly stretched Riga wall by implementing Cattaneo-Christov heat flux model. Viscous dissipation is carried out in Cattaneo-Christov diffusion analysis for the first time in this letter. As a result of Cattaneo-Christov model, some extra terms of viscous dissipation are appeared in the energy equation. These extra terms of viscous dissipation are missing in the literature. On the utilization of suitable transformations, the equations governing the problem are reduced under the boundary layer approximation into the non-linear and dimensionless ordinary differential equations. Convergent approach is utilized to solve the dimensionless governing equations. The solution thus acquired is used to highlight the effects of emerging parameters on velocity distribution and fluidʼs temperature through the graphs. Features of the drag force (or skin friction co-efficient) are graphically interpreted. It is noticed that the presence of modified Hartman number helps to reduce the fluidʼs temperature but enhances the velocity profile. Further an enlargement in the value of thermal time relaxation parameter helps to decrease the temperature distribution.